2011
DOI: 10.1590/s1516-44462011000400004
|View full text |Cite
|
Sign up to set email alerts
|

Concession of sickness benefit to social security beneficiaries due to mental disorders

Abstract: Objective: Assess the odds of having an initial claim for statutory sickness benefit awarded (ascribed to mental disorder as the main registered diagnosis), in relation to institutional, clinical, sociodemographic and welfare factors in Juiz de Fora-MG, Brazil. Method: Two models of logistic regression, taking into account the categories of the medical examiners, were built with the aim of characterizing the relative weight of several variables affecting the medical conclusion. Results: The factors more strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Long-term illnesses were more clearly defined, with studies collectively demonstrating a general shift towards using the ICF model when determining the eligibility of applicants. [48][49][50] However, 27 studies showed that degrees of incapacity remain challenging to categorise objectively, stating that criteria were often inconsistent and unclear. 22 51 legal protections against illness-induced poverty The majority of LMICs have policies stipulating varying levels of illness-related income protection for sickness, work-related injury or disability .…”
Section: Conceptualising Ill Healthmentioning
confidence: 99%
“…Long-term illnesses were more clearly defined, with studies collectively demonstrating a general shift towards using the ICF model when determining the eligibility of applicants. [48][49][50] However, 27 studies showed that degrees of incapacity remain challenging to categorise objectively, stating that criteria were often inconsistent and unclear. 22 51 legal protections against illness-induced poverty The majority of LMICs have policies stipulating varying levels of illness-related income protection for sickness, work-related injury or disability .…”
Section: Conceptualising Ill Healthmentioning
confidence: 99%
“…A large number of outpatient consultations and re-hospitalization rates [ 15 ], difficulty in maintaining a job [ 6 ], and claims for sickness/disability benefits at an early age [ 16 ] are some factors that place schizophrenia amongst the most costly illnesses in the world [ 17 ]. In Brazil, cost estimates for the public health system in the most economically developed State (São Paulo) indicate that schizophrenia costs correspond to 2.2% of its total expenditure on health [ 18 ].…”
Section: Introductionmentioning
confidence: 99%